Advances in information technology : 6th international conference, IAIT 2013, Bangkok, Thailand, December 12-13, 2013. Proceedings - Charoenkitkarn, Nipon; Vanijja, Vajirasak; Chongsuphajaisiddhi, Vithida (Communications in Computer and Information Science,, 2013)
This book constitutes the proceedings of the 6th International Conference on Advances in Information Technology, IAIT 2013, held in Bangkok, Thailand, in December 2013. The 23 revised papers presented in this volume were carefully reviewed and selected from numerous submissions. They deal with all areas related to applied information technology.